Stepping Together with Digital Technology in Merdeka Belajar: Children's Animation Adventure in Drawing at Al Azhar Rawamangun Kindergarten through Project Based Learning-based Animated Drawings application - Tri Rahayu Budiarti (Journal of Childhood Development, 2023)
This study aims to explore and analyze the implementation of Animated Drawings (AD) method based on Project-Based Learning (PBL) in differentiation learning at Al Azhar Rawamangun Kindergarten. This method aims to improve children's engagement and learning outcomes in drawing and understanding concepts through animation. This research uses a qualitative approach with a case study research design. Learning through AD focuses on developing creativity, social skills and the application of digital technology at an early age. During implementation, students are involved in animation projects, allowing them to bring their ideas, interests and creativity into their daily learning. A differentiation approach is used to accommodate students' individual learning styles. The results show that the implementation of PBL-based AD method is effective in improving students' learning interest, creativity, and comprehension ability. Students show high enthusiasm, are actively involved in collaboration, and gain deeper understanding through hands-on experience in creating animations. The importance of the teacher's role as a facilitator and supervisor of student activities in this learning process is a key aspect. The findings of this study provide insights for the development of more interactive project-based learning methods and support the use of digital technology at the early childhood education level.